PERTUMBUHAN UDANG PUTIH (Penaeus merguiensis de Man 1888) DI PERAIRAN ESTUARI SUAKA MARGASATWA KARANG GADING KABUPATEN DELI SERDANG - Anggi Abdur Rohim; Desrita Desrita (AQUACOASTMARINE, 2018)
The aim of this research is to determine the abundance and growth of White Shrim (Penaeus merguiensis de Man 1888) in estuaries of Suaka Margasatwa Karang Gading of Deli Serdang Regency. Sampling was carried out at 3 research stations and for 60 days starting from March to May 2018. White Shrim was caught with fishing gear mini trawl ring. Water quality measurements was carried out in situ. Overall, the condition of the estuaries of Suaka Margasatwa Karang Gading of Deli Serdang Regency was still above the water quality standard. The highest abundance occurs in station I, but the abundance of all the stations has many individuals. The value of the length and weight of White Shrimp at each station was allometric negative with a value of b <3 and the condition factor value of each station shows a value of FK> 1, which indicates that the condition of White Shrimp in estuaries of Suaka Margasatwa Karang Gading of Deli Serdang Regency can morphologically said to have a good fortune.Keywords: Abundance, Estuaries, Growth, White Shrimp